Analisis Penerapan Bauran Pemasaran dan Promosi Digital Marketing pada Dirgantara Travel - Henny Henny (Universitas 45 Surabaya, 2024)
This study discusses the relationship between the marketing mix and digital marketing promotion. Researchers observed that the marketing mix and digital marketing promotion have an effective role in supporting progress in the business unit that is the object of research. The purpose of this study is to identify the application of the marketing mix and digital marketing promotion strategies to be able to advance the business that has been carried out sustainably. Dirgantara Travel Business is a travel agent business that provides airline tickets and accommodation. The method used in this study is a qualitative research method with a descriptive approach as a source of relevant data on the marketing mix and digital marketing promotion. Dirgantara Travel Business applies a marketing mix and digital marketing promotion by reflecting 4 (four) elements of the marketing mix, namely product, price, place and promotion. The results of the study show that the marketing mix and digital marketing system are able to increase Dirgantara Travel's business income. The percentage increase in airline ticket and accommodation reservations in 2020 was 27.3%, and in 2021 it was 27.8%, while in 2022 it was 30.2% and in 2023 it was 35.9%. So the increase in business income shows that Dirgantara Travel has the opportunity to further develop its business.